Complementary and alternative medicine (CAM) providers' views of chronic low back pain patients' expectations of CAM therapies: a qualitative study - Schafer Lisa M; Hsu Clarissa; Eaves Emery; Ritenbaugh Cheryl; Turner Judith; Cherkin Daniel C; Sims Colette; Sherman Karen J (BMC, 2012)
Abstract Background Some researchers think that patients with higher expectations for CAM therapies experience better outcomes and that enthusiastic providers can enhance treatment outcomes. This is in contrast to evidence suggesting conventional medical providers often reorient patient expectations to better match what providers believe to be realistic. However, there is a paucity of research on CAM providers' views of their patients' expectations regarding CAM therapy and the role of these expectations in patient outcomes. Methods To better understand how CAM providers view and respond to their patients' expectations of a particular therapy, we conducted 32 semi-structured, qualitative interviews with acupuncturists, chiropractors, massage therapists and yoga instructors identified through convenience sampling. Interviews were recorded, transcribed and analyzed thematically using Atlas ti version 6.1. Results CAM providers reported that they attempt to ensure that their patients' expectations are realistic. Providers indicated they manage their patients' expectations in a number of domains- roles and responsibilities of providers and patients, treatment outcomes, timeframe for improvement, and treatment experience. Providers reported that patients' expectations change over time and that they need to continually manage these expectations to enhance patient engagement and satisfaction with treatment. Conclusions Providers of four types of CAM therapies viewed patients' expectations as an important component of their experiences with CAM therapy and indicated that they try to align patient expectations with reality. These findings suggest that CAM providers are similar in this respect to conventional medical providers.